1986
DOI: 10.1002/j.1460-2075.1986.tb04208.x
|View full text |Cite
|
Sign up to set email alerts
|

Homologous chromosome recombination generating immunoglobulin allotype and isotype switch variants.

Abstract: We investigated whether spontaneous isotype switching in monoclonal antibody‐producing hybridomas always occurs with genes on the same chromosome. Spleen cells of (BAB/ 25 X AKR/J) F1 mice, immunized with dansyl‐keyhole limpet hemocyanin (DNS‐KLH), were hybridized with NS‐1 to generate hybridomas producing monoclonal anti‐DNS antibodies of either the b or d haplotype of the BAB/25 or AKR/J parent, respectively. We selected isotype switch variants of such hybridomas using the fluorescence‐activated cell sorter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 47 publications
(28 reference statements)
0
13
0
Order By: Relevance
“…Even though 4A5 binds to ROR1 with nearly an order of magnitude higher affinity than D10, this mAb is less effective in inhibiting the growth of ROR1 × TCL1 leukemia cells in vivo. It appears unlikely that this is due to differences in antibody subclass, as the heavy chain constant region isotype of D10 or 4A5 is IgG2 a or IgG2 b , respectively, each of which could direct antibody-dependent cellular cytotoxicity (36)(37)(38). Instead we hypothesize that the activity of each mAb also may be influenced by how each mAb binds to ROR1, which The bars represent the mean number for each group ± SEM; n = 3; *P < 0.05, **P < 0.01, compared with the mIgG group, as calculated using the Student t test.…”
Section: Discussionmentioning
confidence: 99%
“…Even though 4A5 binds to ROR1 with nearly an order of magnitude higher affinity than D10, this mAb is less effective in inhibiting the growth of ROR1 × TCL1 leukemia cells in vivo. It appears unlikely that this is due to differences in antibody subclass, as the heavy chain constant region isotype of D10 or 4A5 is IgG2 a or IgG2 b , respectively, each of which could direct antibody-dependent cellular cytotoxicity (36)(37)(38). Instead we hypothesize that the activity of each mAb also may be influenced by how each mAb binds to ROR1, which The bars represent the mean number for each group ± SEM; n = 3; *P < 0.05, **P < 0.01, compared with the mIgG group, as calculated using the Student t test.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is little evidence that the normal switching mechanism in mice might promote interchromosomal recombinations; only one such possible event has been reported (37), found in a transformed cell line that undergoes switching during cell culture. If, as seems more likely, transgene switching is a two-step process that begins with an interchromosomal homology-based recombination event, then our results indicate that this homologous recombination does not require Rad54.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, both in vivo and in vitro somatic cells were shown to undergo recombinational events, resulting in the emergence of homozygous cells from wild-type heterozygous cells. Recombination between homologous chromosomes has been described in hybrids of CHO cells (4) and most recently in some instances of immunoglobulin class switching (6).…”
Section: Discussionmentioning
confidence: 99%
“…Although recombination between homologous chromosomes in somatic mammalian cells has been difficult to demonstrate (1,2), several recent reports (3)(4)(5)(6) have shown that it can occur. Cavenee et al (3) described a human retinoblastoma in which, following a recombination between the homologous chromosome 13s, the Rb-i and distal loci had become homozygous while proximal loci were still heterozygous.…”
mentioning
confidence: 99%